Big trouble in Little China [videorecording (DVD)] - Russell, Kurt; Dun, Dennis; Cattrall, Kim; Hong, James; Wong, Victor; Burton, Kate; Wong, Carter, 1947- (Twentieth Century Fox Home Entertainment, 2002)
Jack Burton is a big-talking, wisecracking trucker who goes beneath the streets of San Francisco's Chinatown to battle an army of spirits when his friend's fiancee is kidnapped.